EDUKASI LITERASI KEUANGAN DAN PENGELOLAAN DANA BEASISWA KIP KULIAH BAGI MAHASISWA IAIN LANGSA UNTUK MENCEGAH PERILAKU KONSUMTIF - Zikriatul Ulya; Muarif Setiawan; Khairatun Hisan; Ilham Juliyannur; Rafiza Zuliani; Zulhilmi; Wahyuni; Nasruddin; Aulia Husniati; Husni (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2026)
The management of Indonesia Smart Card for Higher Education (KIP Kuliah) scholarship funds is an essential factor in supporting students' academic success. However, some KIP Kuliah recipients at IAIN Langsa have not yet managed their scholarship funds optimally, resulting in spending that is not fully aligned with priority needs and increasing the risk of consumptive behavior. This activity aimed to enhance students' understanding of financial management through budget planning, appropriate fund allocation, and the establishment of spending priorities. A descriptive qualitative approach was employed using observation, structured interviews, and documentation involving one Academic Affairs staff member and eight KIP Kuliah scholarship recipients selected through purposive sampling. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that 62.5% of the students had prepared a budget plan before utilizing their scholarship funds, while 37.5% had not yet developed a systematic financial plan. Most of the scholarship funds were allocated to academic and living expenses, including meals, transportation, books, photocopying, and internet access. Nevertheless, some students still tended to use part of the funds for consumptive purposes that were not aligned with the objectives of the scholarship program. The activity contributed to increasing students' awareness of the importance of financial literacy, budgeting, and responsible scholarship fund management. Continuous financial literacy assistance provided by higher education institutions is expected to strengthen students' financial independence and optimize the utilization of KIP Kuliah scholarship funds to support their academic achievement.